2021
DOI: 10.1002/evl3.261
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic evidence for a trade-off between germline proliferation and immunity inDrosophila

Abstract: Life-history theory posits that investment into reproduction might occur at the expense of investment into somatic maintenance, including immune function. If so, reduced or curtailed reproductive effort might be expected to increase immunity. In support of this notion, work in Caenorhabditis elegans has shown that worms lacking a germline exhibit improved immunity, but whether the antagonistic relation between germline proliferation and immunity also holds for other organisms is less well understood. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 87 publications
0
8
0
Order By: Relevance
“…Female mosquitoes’ reproductive output has been positively correlated with nutritional reserves during the previtellogenic resting stage of oogenesis [56,57]. Fertility and fitness have been linked in insects, particularly in regards to immunity [58,59]. Artificial selection experiments in Drosophila showed that selecting for increased lifespan extends adult survivorship but decreased early reproduction and vise-versa [60].…”
Section: Discussionmentioning
confidence: 99%
“…Female mosquitoes’ reproductive output has been positively correlated with nutritional reserves during the previtellogenic resting stage of oogenesis [56,57]. Fertility and fitness have been linked in insects, particularly in regards to immunity [58,59]. Artificial selection experiments in Drosophila showed that selecting for increased lifespan extends adult survivorship but decreased early reproduction and vise-versa [60].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we observed transcriptional signatures of ER stress in the MI females, consistent with a previous report that described ER stress upon infection in D. melanogaster [ 29 ]. Previous studies that used whole flies to interrogate the transcriptional response to mating (e.g., [ 28 , 30 ]) or infection (e.g., [ 10 ]) have not highlighted ribogenesis genes as a category that change expression substantially in response to infection. A probable explanation may be that the suppressed ribogenesis occurs primarily in the fat body and is masked in samples derived from whole flies.…”
Section: Discussionmentioning
confidence: 99%
“…This can potentially free up resources, that would otherwise have been invested in oogenesis, and even in times of resource scarcity, help maintain other organismal functions (such as immune function) at their optimal levels. Ablation of germline, and therefore the resource sink , has been previously shown to improve immune function in flies (Short et al 2012, Rodrigues et al 2021)…”
Section: Discussionmentioning
confidence: 99%